Face Of The Nation: Articulating A New Image Of Korea And Taiwan Through Regionally Popular Celebrities - Sang , Yeon (Penerbit Universiti Sains Malaysia (USM Press), 2015)
The rapid spread of popular culture within East Asia has motivated the government of each nation to promote its national image to attract tourists. This dynamic cultural exchange has not only brought these nations closer to each other, but has heightened competition in projecting new national identities through visual images projected through promotional tourism videos. This paper elaborates how Taiwan and South Korea are using regionally popular celebrities to foster local identity configurations that simultaneously reach out beyond national borders and revise longstanding ideas about the nature of their populations. Through interviews with the Korean Tourism Organization (KTO) of South Korea and the Tourism Bureau in the Ministry of Transportation and Communications of the Republic of China and analysis of cultural promotional videos such as Trip to the Heartwarming Country of Korea (released in 2010 in South Korea), Haru (released in 2011 in South Korea) and Taiwan Touch Your Heart (released in 2009 in Taiwan), I demonstrate that, through visual imagery in fashioning cultural ideals to be projected in tourist markets, Korea and Taiwan are trying to reconstruct and rebrand their national images to promote their interests. Both governments make marketing via the Korean wave a crucial part of their appeal for cultural tourism. By featuring regionally popular local celebrities, they are following strategies to promote their international standing through the dissemination of newly rearticulated national images. South Korea emphasises the quality and appeal of its popular culture, while Taiwan emphasises the openness and enthusiasm of Taiwanese towards popular foreign products and people.